Measuring food availability and accessibility among adolescents: Moving beyond the neighbourhood boundary. (May 2015) - Shearer, Cindy; Rainham, Daniel; Blanchard, Chris; Dummer, Trevor; Lyons, Renee; Kirk, Sara
Abstract: Geographic methods have provided insight about food location availability and accessibility in understanding neighbourhood variations in health. However, quantifying exposure to food locations within a pre-defined range of an individual's residence ignores locations outside of the residential neighbourhood encountered in daily life. Global positioning system (GPS) data enables exploration of multiple contextual influences on health. This study defines place in relation to behaviour, employing GPS data to 1) describe adolescent food environments within and outside of the residential buffer, 2) quantify actual food location visits, and 3) explore associations between availability and accessibility of food locations and dietary intake. Adolescents ( N = 380; ages 12–16), wore GPS loggers for up to seven days. Availability and accessibility of food locations were defined by counts and distances to food locations within a 15-min walk (1 km) of home, as well as within 50 m of an adolescent's GPS track. We compared the proportion of food locations within the residential buffer to the proportion outside but within the GPS buffer. These proportions were compared to counts and distances to food locations actually visited. We explored associations between food location availability and accessibility with dietary intake variables. Food location availability and accessibility was greater and visits occurred more commonly outside of the residential buffer than within it. Food location availability and accessibility was greater for urban than suburban and rural adolescents. There were no associations between home-based measures of availability and accessibility and dietary intake and only one for GPS-based measures, with greater distance to convenience stores associated with greater fruit and vegetable consumption. This study provides important descriptive information about adolescent exposure to food locations. Findings confirm that traditional home-based approaches overestimate the importance of the neighbourhood food environment, but provide only modest evidence of linkages between the food environment beyond the residential neighbourhood boundary and dietary intake. Highlights: GPS data logging enables measurement of food locations beyond the home neighbourhood. Adolescents' exposure to food locations is greater outside of the home neighbourhood. Adolescents frequently visit food locations outside of the home neighbourhood. A modest association was found between exposure to food locations and dietary intake.